POLA TANAM OPTIMAL PADA LAHAN PANTAI DI KABUPATEN KULONPROGO - Letari Rahayu Waluyati (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2001)
The objective of this study is to observe the optimal crops pattern of coastal land in Kulon Progo district. Selection of the location is used purposive method at six villages within four sub-district which have coastal land such as Temon, Wates, Panjatan and Galur. Sixty farmers sampling were taken as purposive method for several plant pattern of coastal land.The result showed that most commodities are horticulture such as chili, watermelon and peanut. The general problem for planting in the coastal land are water and sea wind. They use water well pump and